The Relationship Between Family Support and Anxiety in Facing Chemotherapy in Breast Cancer Patients at Pelamonia TK II Hospital in Makassar - Jama, Fatma; Alam, Rizqy Iftitah; Lilis, Lilis (International Journal of Halal System and Sustainability https://jurnal.narotama.ac.id/https://www.spb.gba.gov.ar/campus/https://conference.trunojoyo.ac.id/https://ojs.ucp.edu.ar/https://libros.cimsur.unam.mx/https://ojs.stikesmucis.ac.id/http://medi, 2023)
Breast cancer is the most common cancer in women. Chemotherapy is a way of management that can be done in breast cancer patients. Giving chemotherapy can cause physical side effects that have a psychological impact, namely anxiety. Support from family is the most important factor for a person in dealing with health problems and as a preventive strategy in reducing anxiety. This study aimed to determine the relationship between family support and anxiety facing chemotherapy in breast cancer patient at Pelamonia TK II Hospital. The research method used descriptive analytic correlation with a cross sectional study approach. The sample in this study amounted to 48 respondents using total sampling with data collection instruments using a questionnaire sheet. The statistical analysis in this study used an alternative test, namely the Chi Square Test. The results showed that there was a relationship between family support and anxiety facing chemotherapy in breast cancer patients (p value = 0.025), where the p value was less than α = 0.05, then Ha was accepted and H0 was rejected. The conclusion of this study is there is a relationship between family support and anxiety facing chemotherapy in breast cancer patients, meaning that the better family support, the less anxiety. . Therefore, it is expected that nurses will provide positive input to the patient's family regarding the importance of providing support of patients to reduce anxiety facing chemotherapy in breast cancer patients.